High glucose mediates prooxidant and antioxidant enzyme activities in coronary endothelial cells - Bayraktutan, Ulvi; Weidig, Pamela; McMaster, Dorothy; Ulker, Sibel (Blackwell Publishing, 2004)
Objective: Excess levels of free radicals such as nitric oxide (NO) and superoxide anion (O2-)are associated with the pathogenesis of endothelial cell dysfunction in diabetes mellitus. This study was designed to investigate the underlying causes of oxidative stress in coronary microvascular endothelial cells (CMEC) exposed to hyperglycaemia.